TRANSFORMASI DIGITAL PENGELOLAAN KEGIATAN WARGA DI LINGKUNGAN RT/RW BERBASIS e-DASHBOARD - Joko Minardi; Anggit Abdullah (UNIVERSITAS STEKOM, 2023)
RT/RW are a community institution that is closest to citizens, and formed through deliberation in the framework of government and community services that are recognized and determined by the Village Government. In the era of information technology, the RT / RW environment is still very little in using information technology to meet the needs of citizens such as RT financial reporting, writing letters, delivering aspirations, and activities agenda in RT neighborhoods. By utilizing information technology in the neighborhood, the communication and activities between the residents and the village apparatus such as the RT head can run effectively. Therefore, a web-based information system is created in the neighborhood of the RT / RW named Smart by using a dashboard panel that can display infographics in RT / RW environments.